2019
DOI: 10.1002/jgh3.12220
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations related to endoscopic treatment of colorectal tumors

Abstract: Background and Aim Genetic indicators of endoscopic resection for colorectal carcinoma remain inconclusive. This study analyzed genetic changes in early colorectal tumors that could inform decisions for endoscopic procedures. Methods A total of 83 colorectal tumors from 81 patients, including adenoma (n = 7), Tis–T1a (n = 22), T1b (n = 14), and advanced carcinoma (n = 40), were analyzed. Tis tumors (n = 16) and some T1 carcinomas (n = 11) were analyzed as mixed adenomas and carcinomas. Lesions were laser‐captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In other words, a V2 finding in the F-V classification may be equivalent to a histologic diagnosis of malignancy or to a potential risk of malignancy because only this finding can allow the identification of mutated bile duct epithelium without histological confirmation of malignancy. Furthermore, in another study, we recently reported similar concepts about the relation between the endoscopic findings of colorectal tumors and genetic abnormalities [33]. Accumulated gene alterations in the adenoma components of colorectal carcinoma could be diagnosed based on irregular surface pattern findings on magnifying endoscopy.…”
Section: Discussionmentioning
confidence: 68%
“…In other words, a V2 finding in the F-V classification may be equivalent to a histologic diagnosis of malignancy or to a potential risk of malignancy because only this finding can allow the identification of mutated bile duct epithelium without histological confirmation of malignancy. Furthermore, in another study, we recently reported similar concepts about the relation between the endoscopic findings of colorectal tumors and genetic abnormalities [33]. Accumulated gene alterations in the adenoma components of colorectal carcinoma could be diagnosed based on irregular surface pattern findings on magnifying endoscopy.…”
Section: Discussionmentioning
confidence: 68%